Achievement Motivation of Children's Rollerskating Athletes by Gender - Romdhona, Albian Cahya; Friskawati, Gita Febria; Karisman, Vicki Ahmad (STKIP Paasundan Press, 2024)
The purpose of this study was to reveal how the achievement motivation of children's roller skating athletes based on gender. The method used is descriptive quantitative through a survey approach. The population in this study amounted to 50 athletes. The sample used amounted to 21 athletes. The sampling technique used Convenience Sampling. This data analysis technique uses percentage analysis. The results of this study indicate that the achievement motivation of female roller skating athletes is in the very good category (13%), good (40%), moderate 27 (%), less (13%), and very less (7%), while the achievement motivation of male athletes is in the very good category (33%), good (0%), moderate (16%), less (16%) and very less (33%). This shows that the achievement motivation of female athletes is higher than the achievement motivation of male athletes.